On Employee Performance: The Impact Of Work Motivation, Work Discipline, And Work Environment - Muh. Ihsan Said Ahmad; Muhammad Islah Idrus; Syamsu Rijal (Universitas 45 Surabaya, 2023)
This study aims to investigate the effects of work environment, work motivation, and work discipline on employee performance at PT Dayana Cipta in Manado. Using a judgment based, non-probability sampling strategy, a purposive sampling technique was used to include 97 employees in the sample. From here on, the analysis technique uses multiple linear regression analysis. According to the study's conclusions, (1) employee performance is unaffected by motivation at work; (2) employee performance is impacted by discipline; (3) employee performance is influenced by the workplace environment; and (4) employee performance is simultaneously impacted by motivation, discipline, and the workplace environment